P-V Centers Behavior in Diamond C(111) Subsurface Layers - Ananina, O.; Severina, Elena (Physics and Chemistry of Solid State, 2016)
Quantum-chemical modeling is used to study the dependence of spin states, geometrical, electronic and energy characteristics of P-V center from its location on the surface of the diamond C(111). The (111) surface of diamond crystal is found to affect the geometrical parameters, charge characteristics and spin density distribution of P-V centers.